Femmes, musulmanes, libanaises du Sud : revendiquer une place par l’islam - Kinda Chaib (Revue des Mondes Musulmans et de la Méditerranée)
Research has been conducted on female activists of the suburbs of Beirut but nothing has been done on the women of South Lebanon, a rural region in direct contact with the Israeli occupation. The women I met introduce themselves as women, Muslims and from South Lebanon: these three parameters are equally important in their discourse. They use the ‘talkin muslim’ (le ‘parler musulman’) in their daily life to build a position different from the one of their mothers’. They invoke characters of Shiite history as much as the contemporary leaders. In doing so, they elaborate an image of what they call their jihad, a complementary of men’s articulation of that concept. They claim a certain independence in their professional life while subscribing to certain traditional practices concerning the division of roles at home.